Rho family GTPase-dependent immunity in plants and animals - Kawano, Yoji; Kaneko-Kawano, Takako; Shimamoto, Ko (Frontiers in Plant Science, 2014)
In plants, sophisticated forms of immune systems have developed to cope with a variety of pathogens. Accumulating evidence indicates that Rac (also known as Rop), a member of the Rho family of small GTPases, is a key regulator of immunity in plants and animals. Like other small GTPases, Rac/Rop GTPases function as a molecular switch downstream of immune receptors by cycling between GDP-bound inactive and GTP-bound active forms in cells. Rac/Rop GTPases trigger various immune responses, thereby resulting in enhanced disease resistance to pathogens. In this review, we highlight recent studies that have contributed to our current understanding of the Rac/Rop family of GTPases and the upstream and downstream proteins involved in plant immunity. We also compare the features of effector-triggered immunity between plants and animals and discuss the in vivo monitoring of Rac/Rop activation.